Iot Based Ware House Fire Safety System Using ARM7 - Anusha, Guggilla; R. Seshagiri Rao, V (International Journal of Engineering and Technology, 2018)
For the protection and safety of the garment plant staff has becoming a biggest issue now a days. The garment plant employees face a lot of problems and broken out of fireplace one of them for sure. The depositors arenâ€™t showing any interest in this sector and importance of this sector is obtaining toneless.Â  In this research a fireplace detection system is propounded and conjointly provides information of the region affected. Here we used ARM7which are embedded with different types of sensors .We provide associate authentication system to avoid warning. The system can instantly send a SMS to the admin. The admin will make sure or deny the information. If the admin make sure breaking out of fire then system can right away raise an alarm and a SMS will be sent to the nearby fire brigade.Â